Chemoprophylactic and therapeutic efficacy of thymol in murine cystic echinococcosis. Issue 5 (October 2015) - Maggiore, M.; Pensel, P.E.; Denegri, G.; Elissondo, M.C.
Abstract Cystic echinococcosis is a zoonotic disease caused by the larval stage of the cestode Echinococcus granulosus. The drugs commonly used against cystic echinococcosis are benzimidazoles. Unfortunately, 20%–40% of cases do not respond favorably to such chemotherapy. Consequently, the search of new therapeutic alternatives such as the use of traditional medicinal plants has been increased. The aim of the current experimental work was to investigate the chemoprophylactic and clinical efficacy of thymol on mice infected with E. granulosus metacestodes. Thymol (40 mg/kg) was administered under two different therapeutic schemes: dosing every 24 h over 20 days and treatment every 12 h for 10 days. Thymol demonstrated efficacy against experimental murine cystic echinococcosis. The chemoprophylactic and therapeutic effects of thymol were comparable to that of albendazole. Due to the lack of toxicity observed in mice at the tested doses; we consider that thymol is a potential alternative to be applied for the treatment of human hydatid disease.